1988
DOI: 10.1093/oxfordjournals.humrep.a136724
|View full text |Cite
|
Sign up to set email alerts
|

Tubal embryo transfer in cynomologus monkeys: effects of hyperstimulation and synchrony

Abstract: To date the main limitation of in-vitro fertilization-embryo transfer (IVF-ET) programmes is that transcervical transfer of embryos results in a rate of low implantation. On the other hand, the technique of gamete intra-Fallopian transfer (GIFT) does not contribute to information on oocyte fertilization rates, and the time of oocyte exposure to sperm may be limited. The development of ultrasonically guided follicular aspiration will allow transfer of embryos generated in vitro to the Fallopian tubes performing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Since the first birth of a rhesus macaque after IVF in the mid-1980s (1), several laboratories have reported successfully obtaining infants of rhesus, cynomolgus monkey, and pigtailed macaque by IVF or ICSI (8)(9)(10)(11)(12)(13)(14). However, the success rate has been low in comparison with that for rodents and humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first birth of a rhesus macaque after IVF in the mid-1980s (1), several laboratories have reported successfully obtaining infants of rhesus, cynomolgus monkey, and pigtailed macaque by IVF or ICSI (8)(9)(10)(11)(12)(13)(14). However, the success rate has been low in comparison with that for rodents and humans.…”
Section: Discussionmentioning
confidence: 99%
“…To date there has been no report using a pronuclear embryo transfer technique for the production of in vitro-fertilized nonhuman primates, including cynomolgus monkey (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). Based on our and other researchers' extensive experiences in producing transgenic mice (15,(18)(19)(20)(21)(22), it is reasonable to postulate that transferring embryos at the pronuclear stage can come with the certain benefits, such as decreasing the risk of losing embryo quality during the course of long-term in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the difficulties associated with mating and natural conception in macaques that make the study of implantation and early pregnancy difficult can be circumvented by the use of IVF/ET. Previous studies have shown some success with IVF/ET procedures in M. fascicularis , with implantation rates of 8.3%–12.0% achieved using 1–4 embryos transferred per recipient during natural cycles [147-149]. …”
Section: Exogenous Relaxin Administration In a Non-human Primate Modementioning
confidence: 99%
“…That estradiol receptors were not detected in any ovarian compartment, except the surface epithelium, during the normal menstrual cycle (Hild-Petito et al, 1988) questions a local role for estradiol during folliculogenesis. Likewise, the re- Balmaceda et al, 1988Wolf et al, 1989Lanzendorf et al, 1990b Ovulation (day 0) estimated as athe day of sex skin breakdown, bfirst time a corpus luteum was identified at laparoscopy, or '24 hours after midcycle LH surge.…”
Section: Periovulatory Eventsmentioning
confidence: 99%